Early Lessons Learned From the WEB Device: Feasibility, Technique and Complications—A Real-Life Experience. (1st September 2019) - Mouchtouris, Nikolaos; Hasan, David M; Saiegh, Fadi Al; Sweid, Ahmad; Zanaty, Mario; Khanna, Omaditya; Chalouhi, Nohra; Tjoumakaris, Stavropoula I; Gooch, M Reid; Rosenwasser, Robert H; Jabbour, Pascal
Abstract: INTRODUCTION: Wide-neck bifurcation cerebral aneurysms have always posed a treatment challenge and have historically required either clip ligation, or stent vs balloon-assisted coil embolization. This predicament led to the development of the newly FDA-approved Woven EndoBridge (WEB) Aneurysm Embolization System (Sequent Medical Inc, Aliso Viejo, California), which is a self-expanding mesh that achieves intrasaccular flow disruption and does not require antithrombotic medications. In this study, we report our experience with the first 29 consecutive aneurysms treated via WEB embolization at 2 high-volume institutions. METHODS: We reviewed our first 27 consecutive patients with 29 cerebral aneurysms who underwent WEB embolization from February to April 2019. We collected data on patient demographics and clinical presentation, aneurysm characteristics, device and procedural details, and functional outcomes. RESULTS: A total of 29 aneurysms were included in our study. Seven patients (24.1%) presented with acutely ruptured aneurysm while the rest were unruptured. The majority of patients (82.8%) required only 1 attempt for successful device deployment, while a stent was necessary as an adjunct treatment in 4 patients (13.7%) due to WEB herniation. Two patients had residual aneurysm that had to undergo additional treatment; one of them underwent second WEB embolization and one underwent clip ligation. One patient with a PICA aneurysm had device dislodgment with injury to the parent vessel Onyx and coils were used to deconstruct the vertebral artery. CONCLUSION: The advent of the WEB device has significantly impacted the surgical decision-making for the treatment of bifurcation, wide-neck aneurysms. We discuss in detail the lessons learned from patient selection, device size selection, technique, and complications from 2 institutions with a high-volume endovascular and microsurgical aneurysm treatment experience.